A Novel Mutation in Human Androgen Receptor Gene Causing Partial Androgen Insensitivity Syndrome in a Patient Presenting with Gynecomastia at Puberty - Koçyiğit, Cemil (J Clin Res Pediatr Endocrinol, 2016)
Partial androgen insensitivity syndrome (PAIS) typically presents with micropenis, perineoscrotal hypospadias, and a bifid scrotum with descending or undescending testes and gynecomastia at puberty. It is an X-linked recessive disorder resulting from mutations in the androgen receptor (AR) gene. However, AR gene mutations are found in less than a third of PAIS cases. A 16-year-old boy was admitted with complaints of gynecomastia and sparse facial hair. Family history revealed male relatives from maternal side with similar clinical phenotype. His external genitalia were phenotypically male with pubic hair Tanner stage IV, penoscrotal hypospadias, and a bifid scrotum with bilateral atrophic testes. He had elevated gonadotropins with a normal testosterone level. Chromosome analysis revealed a 46,XY karyotype. Due to the family history suggesting a disorder of X-linked trait, PAIS was considered and molecular analysis of AR gene was performed. DNA sequence analysis revealed a novel hemizygous mutation p.T576I (c.1727C>T) in the AR gene. The diagnosis of PAIS is based upon clinical phenotype and laboratory findings and can be confirmed by detection of a defect in the AR gene. An accurate approach including a detailed family history suggesting an X-linked trait is an important clue for a quick diagnosis.